From Mahābhārata Warrior to Sacred Ontological Figure: The Deification of Bhīma in the Late Majapahit Merapi-Merbabu Scriptorium - Muhammad Heno Wijayanto; Sofwan Noerwidi; Putu Eka Guna Yasa; Turita Indah Setyani; I Made Suparta (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2026)
This article addresses an unresolved problem in Javanese cultural heritage, namely the persistence of interpretive fragmentation between archaeological data and philological analysis. Focusing on Bhīma’s transformation from an epic warrior in the Mahābhārata to a sacred spiritual entity during the late Majapahit era, the study examines how the Merapi-Merbabu scriptorium reconstructed his identity through a convergence of material sculptural evidence and esoteric textual formulas. Methodologically, the study adopts an interdisciplinary qualitative design combining philological text editing, iconographic analysis, and cross-media interpretation. Two primary corpora are analyzed: a visual-material corpus consisting of the regional Sukuh-Lawu Mountain-style Bhīma statue, and a textual corpus consisting of the Bhīma Swarga manuscripts from the Merapi-Merbabu scriptorium (specifically codices 1 L 234, 1 L 333, 5 L 5, and 9 L 156), alongside the Nawaruci text. The findings show that material survival alone does not restore cultural coherence, as sacred heritage remains fragmented across media. However, cross-media comparison successfully reconstructs recurring iconographic features, such as the pañcanakha (five-clawed nails) and poleṅ (chequered) cloth, and reconnects sculptural evidence with textual memory. This process uncovers a systematic somatic ontology where Bhīma is reinterpreted as the absolute source of breath (ambĕkan), life (urip), and consciousness (pramāṇa). The article argues that the preservation of sacred heritage becomes most meaningful when it moves beyond object visibility toward cultural legibility, allowing the late Majapahit religious identity to remain interpretable across material statues and textual abstractions.